Rekayasa Digitalisasi Pertanian Hidroponik NFT dengan Model Kendali Suhu, pH dan Electrical Conductivity (EC) - Wahyuni, Sri; Wahyudi, Mujib; Rusidy, Amin (Universitas Trunojoyo Madura, 2021)
Madura, which is nicknamed the island of salt, began to develop hydroponics, especially for the fulfillment of vegetables. So far, hydroponic practitioners have always checked the nutrients on their hydroponic plants twice every day to ensure that the plant's nutritional needs are met, besides that the temperature and pH of the water must also be maintained according to plant needs so that plants can grow and develop properly as expected. Controlling the temperature and pH of the water as well as the nutritional needs that are carried out routinely every day by manual method on hydroponic growing media is considered a hassle. Not everyone understands the technical details of care for the ideal conditions of plants that must be maintained, especially for hydroponic beginners. It is necessary to digitize agriculture, through controlling the plant media automatically based on temperature settings, the measurement of nutritional needs and the pH adjusting the types of vegetables planted. Temperature conditions are monitored using a DS18B20 waterproof sensor with a thermoelectric cooler as a temperature stabilizer actuator in ideal conditions. Meanwhile, the nutritional requirements are calculated based on the type of plant, the reading of potential hydrogen (pH) levels by the pH sensor and the electrical conductivity (EC) value by the EC and TDS sensors are continuously responded by the peristaltic pump to determine the amount of solution and ideal nutritional requirements for plant. The control method (PID) which is implemented in active / non-peristaltic pump activities to control temperature, pH of the solution and nutritional needs based on the EC value of the solution is more precise and only a few times an error with an error value ranging from 1 - 2 ml.